Constraints on the evolution of crustal flow beneath Northern Tibet. (19th December 2015) - Le Pape, Florian; Jones, Alan G.; Unsworth, Martyn J.; Vozar, Jan; Wei, Wenbo; Jin, Sheng; Ye, Gaofeng; Jing, Jianen; Dong, Hao; Zhang, Letian; Xie, Chengliang
Abstract: Crustal flow is an important tectonic process active in continent‐continent collisions and which may be significant in the development of convergent plate boundaries. In this study, the results from multidimensional electrical conductivity modeling have been combined with laboratory studies of the rheology of partially molten rocks to characterize the rheological behavior of the middle‐to‐lower crust of both the Songpan‐Ganzi and Kunlun terranes in the northern Tibetan Plateau. Two different methods are adopted to develop constraints on melt fraction, temperature, and crustal flow velocity in the study area. The estimates of these parameters are then used to evaluate whether crustal flow can occur on the northern margin of the Tibetan plateau. In the Songpan‐Ganzi crust, all conditions are satisfied for topography‐driven channel flow to be dominant, with partial melt not being required for flow at temperature above 1000°C. Further north, the Kunlun fault defines the southern boundary of a transition zone between the Tibetan plateau and the Qaidam basin. Constrained by the estimated melt fractions, it is shown that channel injection across the fault requires temperatures close to 900°C. The composition of igneous rocks found at the surface confirm those conditions are met for the southern Kunlun ranges. To the north, the Qaidam basin is characterized by colder crust that may reflect an earlier stage in the channel injection process. In the study area, at least 10% of the eastward directed Tibetan crustal flow could be deflected northward across the Kunlun Fault and injected into the transition zone defining the northern margin of the Tibetan plateau. Key Points: Magnetotelluric models in northern Tibet are combined with laboratory studies Constraints on melt fraction, temperature, and crustal flow patterns are proposed Discussion on proportion of crustal flow injected beneath the Kunlun fault